Ginger and its component shogaol inhibit Vibrio biofilm formation in vitro and orally protect shrimp against acute hepatopancreatic necrosis disease (AHPND) - Chumporn Soowannayan (2020)
© 2019 Elsevier B.V. Specific isolates of Vibrio parahaemolyticus bacteria that cause acute hepatopancreatic necrosis disease (AHPND) colonize and form biofilms on the chitin lining of the shrimp stomach where they release toxins that cause necrosis in the adjacent hepatopancreas. One potential strategy to prevent AHPND is to inhibit biofilm formation in the stomach using feed additives. Thus, we tested ethanolic extracts of ginger (0.2 mg/ml and 2 mg/ml) for their ability to inhibit biofilm formation by an AHPND-causing isolate of V. parahaemolyticus (3HP) using chitosan coated 96-well polystyrene plastic plates to mimic the shrimp stomach lining. The extract significantly (p <.05) inhibited biofilm formation in those plates but did not inhibit cell growth in broth culture in parallel uncoated plates. Subsequent in vivo immersion-challenge experiments using 3HP (10 6 CFU/ml) showed that use of extract-supplemented feed (0.2 mg/g and 2 mg/g) for 7 days prior to challenge protected whiteleg shrimp (Penaeus vannamei) against mortality (40%–60% higher survival) when compared to control shrimp fed un-supplemented feed. Extract supplementation had no apparent negative effect on feed palatability or on shrimp growth. Three potentially bioactive compounds known to occur in ginger extracts (6-gingerol, 8-gingerol, and 6-shogaol) were also tested for efficacy in biofilm inhibition in vitro, and 6-shogaol was found to be the most potent followed by the others in descending order. None were found to affect bacterial growth in broth. The results of this study suggested that the use of ginger-based or other feed additives that inhibit biofilm formation may constitute a practical approach to reduce the negative impact of AHPND in shrimp aquaculture.